2005
DOI: 10.1073/pnas.0505714102
|View full text |Cite
|
Sign up to set email alerts
|

Mutant mice lacking acetyl-CoA carboxylase 1 are embryonically lethal

Abstract: Acetyl-CoA carboxylases (ACC1 and ACC2) catalyze the carboxylation of acetyl-CoA to form malonyl-CoA, an intermediate metabolite that plays a pivotal role in the regulation of fatty acid metabolism. We previously reported that ACC2 null mice are viable, and that ACC2 plays an important role in the regulation of fatty acid oxidation through the inhibition of carnitine palmitoyltransferase I, a mitochondrial component of the fatty-acyl shuttle system. Herein, we used gene targeting to knock out the ACC1 gene. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
162
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 227 publications
(169 citation statements)
references
References 38 publications
6
162
1
Order By: Relevance
“…This showed that of the two isoforms of acetyl-CoA carboxylase, the enzyme that converts acetyl-CoA into malonyl-CoA, ACC1 is the major, or only, isoform present in the beta cell. ACC1 is the predominant isoform of the enzyme in lipogenic tissues, such as liver and adipose tissue, whereas the other isoform, ACC2, is found in oxidative tissues, such as cardiac muscle and skeletal muscle [18][19][20]. We also observed that rat pancreatic islets and INS-1 832/13 cells possess a fairly high level of fatty acid synthase.…”
Section: Introductionmentioning
confidence: 52%
See 3 more Smart Citations
“…This showed that of the two isoforms of acetyl-CoA carboxylase, the enzyme that converts acetyl-CoA into malonyl-CoA, ACC1 is the major, or only, isoform present in the beta cell. ACC1 is the predominant isoform of the enzyme in lipogenic tissues, such as liver and adipose tissue, whereas the other isoform, ACC2, is found in oxidative tissues, such as cardiac muscle and skeletal muscle [18][19][20]. We also observed that rat pancreatic islets and INS-1 832/13 cells possess a fairly high level of fatty acid synthase.…”
Section: Introductionmentioning
confidence: 52%
“…Malonyl-CoA is also a key regulator of fatty acid oxidation because it is an allosteric inhibitor of carnitine palmitoyltransferase-1 (CPT-1), localized in the outer surface of the inner mitochondrial membrane, where CPT-1 is involved in the transport of long chain acyl-CoAs acids into mitochondria for oxidation. Work from the Wakil group has shown that ACC2 is localized at the mitochondrial membrane, situated so that the malonyl-CoA it synthesizes controls the transport of long chain fatty acyl-CoA by the membrane bound CPT-1 [18,19]. Wakil's data are consistent with ACC1 producing malonyl-CoA for lipogenesis and ACC2 producing malonyl-CoA for inhibition of long chain acyl-CoA uptake and their oxidation into mitochondria [18,20].…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…ACC1, on the other hand, is an essential enzyme responsible for fatty acid synthesis in lipogenic tissues (liver and adipocytes). Deletion of the ACC1 gene in mice is embryo-lethal and has a pronounced effect on liver and adipose tissue lipid metabolism (16)(17)(18). Furthermore, lipogenesis is up-regulated in many tumors, increasing demand for ACC-made malonyl-CoA (19).…”
Section: Fatty Acid Metabolism | Human Healthmentioning
confidence: 99%